CORRELATION BETWEEN UNDERSTANDING OF USING SIMPLE PAST TENSE AND THE ABILITY OF WRITING RECOUNT TEXTS OF THE TENTH YEAR STUDENTS OF SMA 1 MARAWOLA - Nurafiyat Ekamurti (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Dampal Selatan, 2018)
The objective of this research was to find out the correlation between understanding of using simple past tense and the ability of writing recount texts of the tenth year students of SMA I Marawola. The research question was “Is there any significant correlation between understanding of using simple past tense and the ability of writing recount texts of the tenth year students of SMA I Marawola? The population consisted of five paralled classes. Each class consists of 34 to 36 students. To choose the sample, she took the sample by using cluster sampling method. To analyze the data, she applied the formula of Arikunto (Pearson Product Moment Correlation). The result of the data showed that there was no correlation between understanding of using simple past tense and the ability of writing recount text of the tenth year students of SMA I Marawola. It was proved by the result of rxy = 0.13. It means that understanding of using simple past tense and the ability of writing recount text are not correlated. It was caused by some factors. They are some of the students got difficult to change the irregular verb when constructed recount texts, they had lack vocabulary so they had problem in understanding of using simple past tense and writing recount text, and they also had different background english since they were junior high school.